전산화단층촬영을 통한 정상 한국인과 백인의 안와 구조의 비교 - 정현철, 안희배 (Daihan angwa haghoi jabji, 2015)
목적: 정상 한국인과 백인을 대상으로 전산화단층촬영을 이용한 안와부 계측을 시행하여 한국인과 백인에서 안와의 구조적 차이를비교해 보고자 하였다. 대상과 방법: 2009년 1월부터 본원에서 안와전산화단층촬영을 시행한 안과적 질환의 기왕력이 없는 환자들 중 한국인 22명 44안, 백인 22명 44안을 대상으로 안와전산화단층촬영 사진을 2명의 연구자가 후향적으로 분석하였다. 열 가지의 길이 척도와 세 가지의각도 측정을 통해 한국인과 백인의 차이를 비교하였다. 결과: 한국인의 전측내안와 간 거리는 24.05 ± 2.00 mm, 백인은 21.96 ± 1.96 mm였다. 전측안와수직길이는 한국인이 34.19 ± 1.67 mm, 백인이 35.03 ± 1.18 mm로 나타났다. 전측내안와 간 거리와 전측안와수직길이는 두 군 간에 통계적으로 유의한 차이를보였다. 안와 간 각도는 한국인이 47.69o ± 1.49o, 백인이 46.15o ± 2.19o로 나타났고 두 군 간에 통계적으로 유의한 차이를 보였다. 결론: 안와의 입구 부분이 백인에 비해서 좁고, 안와 사이가 더 벌어져 있음을 확인할 수 있었고, 이는 안와 질환이나 기형의 진단, 수술에 도움이 될 것으로 생각된다. Purpose: In this study we analyzed and compared the orbital anatomy in Korean and Caucasian subjects using computed tomography (CT) measurements. Methods: Two observers performed a cross-sectional, retrospective analysis of 44 CT scans of subjects (22 Koreans, 22 Caucasians) with no appreciable orbital or globe disease. Ten length measurements and 3 angle measurements of various orbital aspects were obtained. Analysis was performed to determine if changes in these parameters were associated with race. Results: Anterior medial interorbital length was 24.05 ± 2.00 mm in Korean and 21.96 ± 1.96 mm in Caucasian subjects. Anterior vertical orbital length was 34.19 ± 1.67 mm in Korean and 35.03 ± 1.18 mm in Caucasian subjects. The anterior medial interorbital length and anterior vertical orbital length (p < 0.05) were significantly different. Interorbital angle was 47.69o ± 1.49o in Korean and 46.15o ± 2.19o in Caucasian subjects; the difference was statistically significant (p < 0.05). Conclusions: Compared with Caucasians, the orbit of Korean subjects has a narrower orbital opening and longer interorbital distance. The present study regarding the anatomy of Korean and Caucasian orbits will assist physicians with the evaluation and treatment of orbital diseases. KCI Citation Count: 1